ATIM-03. ANTI-TGFß2 RNA THERAPEUTIC OT-101 INDUCES DURABLE OBJECTIVE RESPONSES IN PATIENTS WITH RECURRENT/REFRACTORY (R/R) GLIOBLASTOMA MULTIFORME (GBM, WHO GRADE 4) OR ANAPLASTIC ASTROCYTOMA (AA, WHO GRADE 3). (11th November 2019) - Uckun, Fatih; Qazi, Sanjive; Hwang, Larn; Nam, David; Trieu, Vuong
Abstract: BACKGROUND: High-grade gliomas (HGG) are characterized by a T-cell exhaustion signature and pronounced T-cell hyporesponsiveness of their tumor microenvironment (TME). Transforming growth factor beta 2 (TGF-ß2) has been implicated as a key contributor to the immunosuppressive landscape of the TME in HGG. OT-101 is a first-in-class RNA therapeutic designed to abrogate the immunosuppressive actions of TGF-ß2. Here we report the single-agent activity of OT-101 in adult patients with R/R HGG. METHODS: In this phase 2 clinical trial (NCT00431561), OT-101 was administered with an intratumoral catheter using a convection enhanced delivery (CED) system. 77 patients received 4–11 cycles of OT-101 via continuous infusion over 7d. Response determinations were based on central review of MRI scans by an independent review committee according to standard and modified McDonald criteria. Standard statistical methods were applied for the analysis of data. RESULTS: The median progression-free survival (PFS) and overall survival (OS) were 86d and 432d, respectively. 26 patients (33.8%) had marked reductions of their tumor volume after receiving OT-101: 19 achieved durable objective responses (CR: 3, PR: 16). The median time for 90% reduction of the baseline tumor volume was 11.7 months (Range: 4.9–57.7 months). The mean log reduction of the tumor volume was 2.2 ± 0.4 (Median = 1.4: Range: 0.4–4.5) logs. 7 had stable disease (SD) lasting > 6 months. The median PFS (1109d [95% CI: 992 - > 1423] vs. 37d [95% CI: 35 – 59] (Log-rank Chi Square = 69.9, P-value < 0.0001) and OS (1280d [95% CI: 1116- > 1743] vs. 240d [95% CI: 169 – 361] (Log-rank Chi Square = 47.0, P-value < 0.0001) of these 26 patients was significantly better than the PFS or OS of the remaining 51 patients. CONCLUSION: Anti-TGFß2 RNA therapeutic OT-101 exhibits clinically meaningful single-agent activity and induces durable CR/PR/SD in R/R HGG patients.